The Consumer Buying Decisions at PT. Supermarket Maju Bersama Medan Denai Branch, North Sumatra Based on Service Quality and Attitude - Nita Zahara; Abd. Rasyid Syamsuri (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The purpose of this study is to examine how service attitudes and quality affect consumer buying decisions at the PT. Maju Bersama Supermarket, Medan Denai Branch, North Sumatra. 9.180 shoppers from January to April 2022 made up the study's population. 99 clients made up the research sample, which was determined using the Slovin formula with an e value of 10%. This study employs a quantitative methodology and collects data through questionnaires, study documentation, and observation. Multiple linear regression using the statistical product software solution (SPSS) program is the method used for the analysis of the research. The study's findings demonstrate that service quality influences purchases in a positive and significant way. Buying decisions are positively and significantly impacted by attitude. At PT. Maju Bersama Supermarket, Medan Denai Branch, North Sumatra, customer buying decisions are positively and significantly impacted by overall service quality and attitude. The measured coefficient of determination (R2) is 0.636 in value. This demonstrates that service quality and attitude can account for 63.6 percent of purchasing choices.